2019
DOI: 10.1097/md.0000000000016548
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness and safety of transvenous extraction of single- versus dual-coil implantable cardioverter-defibrillator leads at single-center experience

Abstract: The available literature lacks data concerning direct comparison of the effectiveness and safety of single- versus dual-coil implantable cardioverter-defibrillator (ICD) leads transvenous extraction. Certainly, additional shocking coil in superior vena cava adds to the amount of metal in the vascular system. Adhesions developing around the superior vena cava coil add to the difficulty of extraction of ICD lead if lead removal is required. The aim of the study was to assess the effectiveness and safety of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…As reported in the literature, removing ICD leads, particularly the dual -coil ones, increases fluoroscopy time and requires more advanced equipment. 13 The fluoroscopy time only during the PPM lead extraction was similar in both groups. As shown in our previous study, the older age of leads is also a major predictor of long fluoroscopy during TLE, 17 whereas in the current study, we observed a similar age of extracted leads in both groups.…”
Section: What's New?mentioning
confidence: 77%
See 2 more Smart Citations
“…As reported in the literature, removing ICD leads, particularly the dual -coil ones, increases fluoroscopy time and requires more advanced equipment. 13 The fluoroscopy time only during the PPM lead extraction was similar in both groups. As shown in our previous study, the older age of leads is also a major predictor of long fluoroscopy during TLE, 17 whereas in the current study, we observed a similar age of extracted leads in both groups.…”
Section: What's New?mentioning
confidence: 77%
“…In line with these findings, our previous analysis showed that the extraction of dual -coil ICD leads was as safe and effective as the extraction of a single -coil ICD lead, but it required longer fluoroscopy time and frequent use of advanced tools. 13 Importantly, the number of extracted leads at the index procedure was associated with an increased all -cause mortality rate within 30 days after TLE both in univariable and multivariable analyses.…”
Section: What's New?mentioning
confidence: 88%
See 1 more Smart Citation
“…The observed low rate of TLE due to infection is consistent with our strategy to rigorously treat pacing-related complications. 3,9,12,13 This approach aligns with the current expert consensus statement. 5 However, in other studies, especially those concerning older electrodes, the dominant indication was infectious complications.…”
Section: Discussionmentioning
confidence: 70%
“…10,14 In our previous study, we demonstrated that extraction of dual-coil ICD leads required more advanced tools and longer fluoroscopy time. 12 Pecha et al showed that extraction of dual-coil ICD leads was associated with longer laser treatment times. 17 Additionally, as proved by The GermAn Laser Lead Extraction RegistrY: GALLERY a lead dwell time ≥10 years was identified as an independent risk factor for procedural failure during laser lead extraction.…”
Section: Discussionmentioning
confidence: 99%